Cultural sport psychology as a pathway to advances in identity and settlement research to practice. (May 2019) - Schinke, Robert J.; Blodgett, Amy T.; Ryba, Tatiana V.; Kao, San Fu; Middleton, Thierry R.F.
Abstract: Objectives: To situate mostly European cultural sport psychology scholarship in a historical backdrop and then to draw on two recent examples from such scholarship to propose future prospects. Design: A review of literature is utilized to situate the recent prominence of cultural sport psychology. This review is written temporally from past, to present, to future prospects. Method: A presentation of scholarship is presented temporally relating to the following: (a) gender scholarship, (b) cross cultural voids in race and ethnicity, (c) situating of cultural sport psychology in present day, with the emergence of European scholars, (d) the topics of intersectionality of identity and acculturation are drawn upon to reveal diverse approaches taken in this line of scholarship and practice, and (e) reflections and recommendations are proposed, calling for openness of perspectives and topic areas. Results: The presentation of scholarship is intended to serve as a form of advocacy for diverse approaches in cultural sport psychology. This advocacy is exemplified through such terms as cultural praxis and decolonization, beyond a broader call for receptiveness for diverse epistemological approaches. Conclusions: Cultural sport psychology is now becoming popular, among both scholars and practitioners. The benefits from such approaches extend beyond advocacy through research to mental health benefits for sport participants and exercisers. Highlights: Overviews the origins of cultural sport psychology from its inception to present day. Draws upon European contributions to the broader trajectories of identity and acculturation scholarship. Advocates for openness to diverse perspectives and topic areas among cultural sport psychology researchers and practitioners. Suggestions are made for the future of cultural sport psychology and how it can continue to be open to differring topics.